Miscarriage Is Not a Cause of Death: A Response to Berg's "Abortion and Miscarriage". Issue 4 (13th July 2021) - Colgrove, Nicholas
Abstract: Some opponents of abortion claim fetuses are persons from the moment of conception. Call these "Personhood-At-Conception" (or PAC), opponents of abortion. Amy Berg (2017, Philosophical Studies 174:1217–26) argues that if fetuses are persons from the moment of conception, then miscarriage kills far more people than abortion. Thus, PAC opponents of abortion must "immediately" and "substantially" shift their attention, resources, etc., toward preventing miscarriage or admit they do not believe that personhood begins at conception (or, at least, they should recognize they are not acting in ways consistent with this belief). Unfortunately, Berg's argument fails at every step. After outlining her argument, I show that her claim—that "miscarriage . . . is much deadlier than abortion"—is false (when taken literally) and misleading otherwise. Further, Berg's argument is identical in structure to a criticism sometimes levied against the "Black Lives Matter" movement. In the latter context, the argument has been vehemently rejected. Berg's argument should be rejected for the same reasons. Finally, Berg cites no evidence when claiming that PAC opponents of abortion are "not doing enough" to prevent miscarriage. And, even if PAC opponents of abortion are not diverting substantial funds toward miscarriage prevention, Berg fails to notice that this may be for good reason.